Cannabinoids in Neurology - Position paper from Scientific Departments from Brazilian Academy of Neurology - Brucki, Sonia Maria Dozzi; Adoni, Tarso; Almeida, Carlos Mauricio Oliveira; Andrade, Daniel Ciampi De; Anghinah, Renato; Barbosa, Luciana Mendonça; Bazan, Rodrigo [UNESP]; Carvalho, Alzira Alves De Siqueira; Carvalho, William; Christo, Paulo Pereira; Coletta, Marcus Della; Conforto, Adriana Bastos; et al. (Academia Brasileira de Neurologia - ABNEURO, 2021)
Cannabinoids comprehend endocannabinoids, phytocannabinoids, and synthetic cannabinoids, with actions both in the central and peripherical nervous systems. A considerable amount of publications have been made in recent years, although cannabis has been known for over a thousand years. Scientific Departments from the Brazilian Academy of Neurology described evidence for medical use in their areas. Literature is constantly changing, and possible new evidence can emerge in the next days or months. Prescription of these substances must be discussed with patients and their families, with knowledge about adverse events and their efficacy.

Os canabinoides compreendem os endocanabinoides, fitocanabinoides e os canabinoides sintéticos e desempenham ações no sistema nervoso central e periférico. Uma quantidade enorme de publicações tem sido lançada nos últimos anos, embora a cannabis seja conhecida por milênios. Os Departamentos Científicos da Academia Brasileira de Neurologia descreveram as evidências do uso médico em suas áreas. A literatura está em constantes mudanças e possíveis novas evidências podem surgir nos próximos dias ou meses. A prescrição dessas substâncias deve ser discutida com os pacientes e suas famílias, com conhecimento sobre eventos adversos e sua eficácia.
Canabinoides em Neurologia - Artigo de posicionamento dos Departamentos Científicos da Academia Brasileira de Neurologia
Keywords: Cannabis; Cannabinoids; Neurology; Cannabidiol; Cannabis; Canabinoides; Neurologia; Canabidiol